3β-Acetyloxy-oleanolic Acid Attenuates Pristane-Induced Lupus Nephritis by Regulating Th17 Differentiation - Xiaoqing Zhou; Huanpeng Chen; Fengjiao Wei; Qingyu Zhao; Qiao Su; Jinhao Liang; Meng Yin; Xuyan Tian; Zhonghua Liu; Bolan Yu; Chuan Bai; Xixin He; et al. (Journal of Immunology Research)
Th17 activity has been implicated in systemic lupus erythematosus (SLE), which is a systemic autoimmune disease with a typical clinical manifestation of lupus nephritis (LN). Retinoic acid receptor-related orphan receptor gamma t (RORγt) has been shown to be important for Th17 differentiation. In this study, we evaluated the inhibition of RORγt activity by 3β-acetyloxy-oleanolic acid (AOA), a small molecule isolated from the root of Symplocos laurina, a traditional herb belonging to South China. We demonstrated that AOA can inhibit RORγt activity and prevent SLE pathogenesis in a pristane-induced LN model. The results showed that AOA decreased RORγt transcription activity in a reporter assay and prevented Th17 differentiation in vitro. In vivo studies showed that AOA treatment decreased serum anti-dsDNA antibody and alleviated renal pathologic damage as well as antibody complex accumulation in the pristane-induced LN model. These results demonstrated that AOA can improve the clinical manifestation of LN, indicating potential application in SLE therapy.